DIFFERENCES IN NON FASTING TRIGLICERIDE LEVELS BETWEEN 8 HOURS FASTING AND 12 HOURS FASTING - Desika Dewi; Dini Puspodewi; Meka Faizal Farabi (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Triglycerides are a type of blood fat that plays an important role in energy metabolism, but excessive levels can increase the risk of cardiovascular disease. The examination of triglyceride levels generally requires fasting, but the optimal duration of fasting is still debatable. This study aims to analyze the differences in triglyceride levels in non-fasting conditions, 8-hour fasting, and 12-hour fasting. This study is an analytical study with a cross sectional design involving 39 students of the Bachelor of Applied Medical Laboratory Technology Study Program at Al-Irsyad University Cilacap as samples. Blood was taken in three conditions: non-fasting, 8-hour fasting, and 12-hour fasting, then examined using the GPO-PAP colorimetric enzymatic method. The analysis showed that the average triglyceride level in the non-fasting condition was 104.59 mg/dL, 8-hour fasting was 91.90 mg/dL, and 12-hour fasting was 87.08 mg/dL. The results of the Paired Sample T-Test test showed that there was a significant difference between non-fasting conditions and 8-hour fasting (p = 0.009), as well as between non-fasting and 12-hour fasting (p < 0.001). However, there was no significant difference between 8-hour fasting and 12-hour fasting (p = 0.172). Based on these findings, it can be concluded that fasting for 8 hours is enough to significantly reduce triglyceride levels, so it can be considered as the minimum feasible duration for triglyceride. Keywords: Triglycerides, Non Fasting, 8 Hours Fasting, 12 Hours Fasting